The impact of exercise on the gut microbiota in middle-aged amateur serious runners: a comparative study - Duan, Rui; Liu, Yu; Zhang, Yonglian; Shi, Jinrong; Xue, Rong; Liu, Ruijie; Miao, Yuanxin; Zhou, Xianfeng; Lv, Yongling; Shen, Hexiao; Xie, Xiongwei; Ai, Xu (Frontiers in Physiology, 2024)
Exercise, health, and the gut microbiota (GM) are strongly correlated. Research indicates that professional athletes, especially ultra-marathon runners, have unique GM characteristics. However, more research has focused on elite athletes, with little attention given to amateur sports enthusiasts, especially those in the middle-aged population. Therefore, this study focuses on the impact of long-term running on the composition and potential functions of the GM in middle-aged individuals.We compared the GM of 25 middle-aged serious runnerswith 22 sedentary healthy controls who had minimal exercise habitsusing 16S rRNA gene sequencing. Additionally, we assessed dietary habits using a food frequency questionnaire.Results and Discussion: Statistical analysis indicates that there is no significant difference in dietary patterns between the control group and serious runners. Diversity analysis results indicate that there is no significant difference in α diversity between the two groups of GM, but there is a significant difference in β diversity. Analysis of the composition of GM reveals that Ruminococcus and Coprococcus are significantly enriched in serious runners, whereas Bacteroides, Lachnoclostridium, and Lachnospira are enriched in the control group. Differential analysis of functional pathway prediction results reveals significant differences in the functional metabolism levels of GM between serious runners and the control group. Further correlation analysis results indicate that this difference may be closely related to variations in GM. In conclusion, our results suggest that long-term exercise can lead to changes in the composition of the GM.These changes have the potential to impact the overall health of the individual by influencing metabolic regulation.